2019
DOI: 10.1111/are.14409
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rearing water depths and feed types on the growth performance of African catfish ( Clarias gariepinus )

Abstract: The suitability of the African catfish (Clarias gariepinus) to aquaculture throughout its distributional range started to be recognized in the middle of the 1980s. Over 30 years later, this species is now farmed either commercially or for subsistence in almost every country in sub-Saharan Africa as well as in North Africa and many other countries around the world (Dauda, Natrah, Karim, Kamarudin, & Bichi, 2018). Given its biology, it is easy to understand the appeal of C. gariepinus for aquaculture. Its abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…hemioliopterus are scarce in the literature. In this study, the animals showed superior performance when compared to other juvenile catfish (Siluriformes), such as Asian red‐tail catfish ( Hemibagrus wyckioides ) (Deng et al ., 2011), yellow catfish ( Pelteobagrus fulvidraco ) (Wu, Zhou, et al ., 2018a), African catfish ( Clarias gariepinus ) (Abdel‐Hay et al ., 2020), hybrid catfish ( Pseudoplatystoma reticulatum × Pseudoplatystoma corruscans ) (Sousa et al ., 2020) and jundiá ( Rhamdia quelen ) (Rodrigues et al ., 2020). Regarding the self‐feeding system, similar performance results were described in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…hemioliopterus are scarce in the literature. In this study, the animals showed superior performance when compared to other juvenile catfish (Siluriformes), such as Asian red‐tail catfish ( Hemibagrus wyckioides ) (Deng et al ., 2011), yellow catfish ( Pelteobagrus fulvidraco ) (Wu, Zhou, et al ., 2018a), African catfish ( Clarias gariepinus ) (Abdel‐Hay et al ., 2020), hybrid catfish ( Pseudoplatystoma reticulatum × Pseudoplatystoma corruscans ) (Sousa et al ., 2020) and jundiá ( Rhamdia quelen ) (Rodrigues et al ., 2020). Regarding the self‐feeding system, similar performance results were described in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Osawe [4] identified good qualities of catfish, such as its survival in different cultural systems and diverse environments. Catfish can grow fast, and the air breathes, which makes it vital to the sustainability of the aquaculture industry in Nigeria [3], [5].…”
Section: Introductionmentioning
confidence: 99%
“…In aquaculture studies, little attention has been paid to tank water level, which is a crucial factor affecting the growth, survival, yield, and welfare of fishes. While there are several studies on the impact of water levels on the survival, growth, and behavior of different fish species in recirculating aquaculture systems (RAS) (Einarsdóttir and Nilssen 1996, Flodmark et al 2004, Koz³owski et al 2009, more attention has been focused on water depths in ponds (El Naggar et al 2006, Ali et al 2013, Hosen et al 2019, Abdel-Hay et al 2020) and the impact of water level fluctuations on the species communities in rivers, lakes, and reservoirs (Kahi et al 2008, Bucat et al 2012. In pikeperch tank water levels might affect its growth, because this species takes feed mainly from the water column (Zakêoe 2009, Koz³owski et al 2014).…”
Section: Introductionmentioning
confidence: 99%